PENGARUH EFISIENSI MODAL KERJA DAN PERTUMBUHAN PENDAPATAN TERHADAP PROFITABILITAS PT ASTRA OTOPARTS TBK TAHUN 2020-2024 - Pulungan, Mutiara (Politeknik Negeri Medan, 2025)
This research analyzes the influence of working capital efficiency and revenue growth on the profitability of PT Astra Otoparts Tbk during the period 2020 to 2024. Utilizing a quantitative descriptive approach , this study aims to map the trends and dynamics among these three variables. Secondary data was obtained from the company's annual financial reports published by the Indonesia Stock Exchange (BEI). Working capital efficiency is measured by the Cash Conversion Cycle (CCC) , revenue growth by the percentage increase in the company's net sales , and profitability by net income The analysis results indicate that in 2020, the company experienced a significant net loss , coinciding with the lowest working capital efficiency (longest cash conversion cycle) and a sharp revenue contraction , suggesting a direct correlation between decreased working capital efficiency, revenue, and profitability. The dramatic recovery in profitability in 2021 and 2022 was supported by an increase in working capital efficiency (shorter cash conversion cycle) and strong revenue growth. However, in 2023 and 2024, despite a slight decrease in working capital efficiency and a slowdown in revenue growth , the company's profitability continued to increase and reached its highest point. This indicates that, in addition to working capital efficiency and revenue growth, other factors such as stricter cost management, operational optimization, or pricing strategies also played a crucial role in supporting profitability. This research confirms that working capital efficiency and revenue growth are important factors affecting the profitability of PT Astra Otoparts Tbk, but this relationship is complex and influenced by various other internal factors.